2010
DOI: 10.1074/jbc.m109.084996
|View full text |Cite
|
Sign up to set email alerts
|

The C Terminus of the Alb3 Membrane Insertase Recruits cpSRP43 to the Thylakoid Membrane

Abstract: The YidC/Oxa1/Alb3 family of membrane proteins controls the insertion and assembly of membrane proteins in bacteria, mitochondria, and chloroplasts. Here we describe the molecular mechanisms underlying the interaction of Alb3 with the chloroplast signal recognition particle (cpSRP). The Alb3 C-terminal domain (A3CT) is intrinsically disordered and recruits cpSRP to the thylakoid membrane by a coupled binding and folding mechanism. Two conserved, positively charged motifs reminiscent of chromodomain interaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
105
6

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(121 citation statements)
references
References 59 publications
10
105
6
Order By: Relevance
“…These data suggested an interaction between cpSRP43 and Alb3 but provided no direct indication of a proteinprotein interaction. Recently, a direct interaction between the recombinant C-terminus of Alb3 and cpSRP43 was proven [13]. However, the physiological role of cpSRP43 in the cpSRP54/ cpFtsY-dependent LHCP transport remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These data suggested an interaction between cpSRP43 and Alb3 but provided no direct indication of a proteinprotein interaction. Recently, a direct interaction between the recombinant C-terminus of Alb3 and cpSRP43 was proven [13]. However, the physiological role of cpSRP43 in the cpSRP54/ cpFtsY-dependent LHCP transport remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Moore et al [7] reported that cpSRP54 and cpFtsY form the translocation interface together with Alb3 and that complex formation required neither cpSRP43 nor LHCP. However, another study showed that Histagged cpSRP43 copurifies with Alb3 from thylakoid membranes [12], and recently, it was shown that the recombinant C-terminus of Alb3 interacts with cpSRP43 [13].…”
Section: Introductionmentioning
confidence: 99%
“…Examples of ID proteins are the A. thaliana ERD10 and ERD14 dehydrin proteins (48,49), the N-terminal region of the A. thaliana Hy5 bZIP transcription factor involved in photomorphogenesis (50), and the Hordeum vulgare (barley) senescence-associated NAC transcription factor (33). In the case of the Alb3 membrane insertase (51) and the DELLA proteins (34), their ID regions mediate protein interactions.…”
Section: Discussionmentioning
confidence: 99%
“…The cpSRP cooperates in a GTP-dependent manner with cpFtsY, an ortholog of the SRP receptor, to deliver LHCP to ALBINO3 (ALB3), an ortholog of the bacterial YidC protein and a member of the Alb3/Oxa1/YidC insertase family. The ALB3 protein then mediates the insertion (and assembly) of the LHCP protein into the thylakoid membrane (Moore et al, 2000;Falk et al, 2010;Dünschede et al, 2011). Accordingly, Arabidopsis alb3 mutants display a strongly chlorotic/albino phenotype linked to defective LHCP biogenesis (Sundberg et al, 1997;Asakura et al, 2008); by contrast, those with defects affecting a second, paralogous protein called ALB4 appear relatively normal, suggesting that this factor is functionally different (Gerdes et al, 2006;Benz et al, 2009;Trösch et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…To address this possibility, we employed in vitro pull-down experiments using recombinant proteins expressed in bacteria ( Figures 6A to 6C). For this work, we used an N-terminally tagged form of the STIC1/ALB4 C terminus (His-ALB4C; residues 345 to 498 of the preprotein), representing most of the stromal C-terminal domain (Falk et al, 2010), and an N-terminally tagged form of the mature STIC2 protein (GST-STIC2; residues 49 to 182 of the preprotein) ( Figure 6A, left side). Equal amounts of soluble lysate from bacteria expressing each protein were mixed together, and then the His-ALB4C protein was affinity purified.…”
Section: Stic2 Interacts With the C Termini Of Alb4 And Alb3 In Vitromentioning
confidence: 99%